Exploring the relationship between ethical and sustainable consumption in short supply chains: A literature review - Santos, M. J. P. L. dos.; Baptistal, N. T.; Nobre, H. (Advances in human factors, business management and leadership. Lecture Notes in Networks and Systems, 2021)
Sustainable development, sustainable consumption and short supply chains are nowadays acquiring increasing relevance in the literature. On the other hand, from the consumer's attitudinal statement, ethical consumption is also requiring more attention from marketing sciences. Besides that, the integration of the last concept on sustainability remains in a complete lack of systematic and integrative conceptualization. This paper tries to promote a potential integration of all the dimensions of sustainable consumption and to understand the potential linkage and interaction among them, in order to promote the Sustainable Development Goal 15 from the United Nations. The methodology follows a systematic literature review and preliminary information comes from a case study of the approved project SDGsConsum. The results confirm that, besides a huge development in sustainable development and sustainable consumption in the literature, the focus on shortly supply chains of production is yet modest. Moreover, the motivations and constraints that drive and restrain, respectively, consumers toward ethical and sustainable consumption presents several incongruences.